Ամուսնական հարաբերությունների և ամուսնության տևողության փոփոխությունները ժամանակակից իրանական ընտանիքում և խնդրի հետազոտման աստիճանը - Նասրին Մոլլայի (ՀՀ ԳԱԱ հրատ.)
Статья посвящена влиянию современных тенденций развития иранской семьи как института на брачные отношения, на удовлетворенность браком, на качество и продолжительность брака и выдвинутым социологами исследовательским задачам и их решениям. Статья демонстрирует возможные и разрешенные микро- и макроуровневые влияния модернизации на иранскую закрытую культурную систему. This article is concerned with the impact of modern trends in institutional developments of families on marital relationships, satisfaction, the quality and the duration of marriages in the contemporary Iranian society. It is as well concerned with the issues and solutions related to the problem that sociologists have put forward. The study gives an opportunity to understand the impact of possible and acceptable micro and macro level of modernization in the Iranian closed cultural system.
Keywords: Sociology; The family; Marriage; Woman